A modified Ti3C2T x Waterborne polyurethane anticorrosive coating and preparation method thereof
By using modified Ti3C2Tx (MXene) composite in water-based polyurethane coatings, the problem of water channel and poor mechanical properties of water-based coatings are solved, and the corrosion and mechanical properties of the coating are significantly improved.
Patent Information
- Application Number
- CN202210360452.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-04-07
AI Technical Summary
The existing water-based polyurethane coatings have water channels after film formation, which cannot provide sufficient long-term protection for metal substrates, especially in strong corrosion environments, and poor interface compatibility with inorganic materials leads to poor mechanical properties.
Modified Ti3C2Tx (MXene) is used to compound in situ with polypyrrole and dopamine to form a PDA-Ppy-Ti3C2Tx (MXene) composite, and it is uniformly dispersed in the aqueous polyurethane to form an aqueous polyurethane anticorrosion coating containing modified Ti3C2Tx.
The barrier, mechanical properties and corrosion resistance of the coating are significantly improved, the oxidation resistance of Ti3C2Tx (MXene) is improved, and the long-term corrosion resistance of the coating is improved through the corrosion inhibition of polydopamine and the passivation of polypyrrole.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer coatings, and particularly relates to a modified Ti3C2T x A water-based polyurethane anti-corrosion coating and a preparation method thereof. Background Art
[0002] Polyurethane coatings have strong corrosion resistance, weather resistance and strong adhesion to metal substrates, and are widely used for corrosion protection of metal substrates. Polyurethane coatings are mainly divided into solvent-based coatings and water-based coatings. Solvent-based polyurethane has good film density and water resistance; however, solvent-based coatings contain a large amount of volatile organic compounds (VOCs), which can cause harm to the environment and human body. In recent years, as people pay more attention to human health and environmental protection, water-based polyurethane coatings have attracted widespread attention because of their green, environmentally friendly and pollution-free properties. However, pure water-based polyurethane coatings will leave water channels after film formation and cannot provide sufficient long-term protection for metal substrates, especially in highly corrosive environments. Organic-inorganic composites are a common method to enhance the corrosion resistance of waterborne polyurethane (WPU) coatings.
[0003] Ti3C2T x (MXene) is a type of inorganic two-dimensional material that has become a research hotspot since it was first prepared by Naguib et al. in 2011. x (MXene) has a large aspect ratio and excellent ion adsorption, and has great application prospects in the field of corrosion protection. x It is added directly or after modification to water-based resin to enhance the corrosion resistance of water-based resin coatings; however, due to the poor interface compatibility between organic and inorganic materials, WPU / inorganic composite coatings have problems such as poor mechanical properties. x It is an urgent problem to solve how to make water-based coatings have good anti-corrosion effect and excellent mechanical properties. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a modified Ti3C2T x Water-based polyurethane anti-corrosion coating.
[0005] Another object of the present invention is to provide the above-mentioned modified Ti3C2T x Preparation method.
[0006] The purpose of the present invention is achieved through the following solutions:
[0007] A modified Ti3C2T xA water-based polyurethane anti-corrosion coating comprising water-based polyurethane, PDA-Ppy-Ti3C2T x (MXene) composites, defoamers, leveling agents, dispersants and other ingredients.
[0008] The modified Ti3C2T x A water-based polyurethane anti-corrosion coating comprising the following components in parts by mass:
[0009]
[0010] The waterborne polyurethane is selected from F0401 or F0402, both of which can be purchased from Shenzhen Yoshida Chemical Co., Ltd., preferably F0401 emulsion;
[0011] The defoamer is a white mineral oil defoamer purchased from Dingsheng Environmental Protection Technology Co., Ltd.
[0012] The leveling agent is a fluorocarbon leveling agent, preferably OP-8035 / KH leveling agent, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0013] The dispersant is an unsaturated polycarboxylic acid polymer solution, preferably BYK163, purchased from BYK Chemical Co., Ltd., Germany;
[0014] A modified Ti3C2T x The preparation method of the waterborne polyurethane anticorrosive coating comprises the following steps:
[0015] PDA-Ppy-Ti3C2T x The (MXene) composite dispersion is added to the aqueous polyurethane emulsion and mixed evenly, and then a defoamer, a leveling agent, and a dispersant are added thereto and mixed evenly to obtain a modified Ti3C2T x Water-based polyurethane anti-corrosion coating.
[0016] The PDA-Ppy-Ti3C2T x (MXene) composite dispersion is prepared by the following steps:
[0017] (1) The pyrrole monomer is completely dissolved in the mixed solution to obtain a polypyrrole dispersion, which is then added to the Ti3C2T x Aqueous dispersion, and the mixture is allowed to stand;
[0018] (2) adding an aqueous solution of ferric chloride to the mixture after standing in step (1) to react, and after the reaction is completed, centrifuging, collecting and washing the bottom precipitate to remove unreacted pyrrole monomer;
[0019] (3) dispersing the precipitate washed in step (2) in water to obtain a dispersion, dissolving tromethamine in the dispersion, and adjusting the pH value of the mixed solution;
[0020] (4) Add dopamine hydrochloride to the mixed solution after adjusting the pH value in step (3) to react. After the reaction is completed, centrifuge and collect the PDA-Ppy-Ti3C2T x The (MXene) precipitate was washed to remove the unreacted dopamine hydrochloride, and finally the precipitate was dispersed in water to obtain PDA-Ppy-Ti3C2T x (MXene) dispersion.
[0021] The mixed solution in step (1) is a mixture of water and ethanol, wherein the volume ratio of water to ethanol is 1:1;
[0022] The amount ratio of the pyrrole monomer and the mixed solution in step (1) satisfies: 0.1-0.5 g of pyrrole monomer is added for every 10 ml of the mixed solution;
[0023] The polypyrrole dispersion and Ti3C2T x The volume ratio of the aqueous dispersion is 1:5;
[0024] The static condition described in step (1) is to place at 4-12° C. for 12-48 hours;
[0025] Ti3C2T described in step (1) x Dispersion refers to the Ti3C2T x Dispersed in water, and ultrasonically treated under N2 protection to obtain 2-4 g / L Ti3C2T x Aqueous dispersion;
[0026] The ferric chloride aqueous solution in step (2) is prepared by adding 0.1-0.5 g of ferric chloride per 10 ml of aqueous solution; the volume ratio of the ferric chloride aqueous solution to the mixture is 1:6;
[0027] The reaction conditions in step (2) are 4-12° C. for 12-48 hours;
[0028] The washing described in step (2) refers to washing the precipitate with water or anhydrous ethanol;
[0029] The amount of water used in step (3) is such that 250 ml of water is added for every 1 g of precipitation;
[0030] The amount of tromethamine used in step (3) satisfies the following conditions: 2.5-7.5 L of dispersion liquid is used for every 3-9 g of tromethamine; preferably, 5 L of dispersion liquid is used for every 6 g of tromethamine;
[0031] The pH value in step (3) is adjusted by 0.1 mol / L hydrochloric acid to a pH range of 8-9;
[0032] The amount of dopamine hydrochloride used in step (4) satisfies: 0.625-3.125 L of the mixed solution is used for every 1-5 g of dopamine hydrochloride; preferably, 0.625 L of the mixed solution is used for every 1 g of dopamine hydrochloride;
[0033] The reaction conditions in step (4) are 4-30° C. for 12-48 h;
[0034] The washing described in step (4) refers to washing the precipitate with water or anhydrous ethanol.
[0035] PDA-Ppy-Ti3C2T described in step (4) x The (MXene) dispersion is preferably 1 g PDA-PANI-Ti3C2T x The (MXene) precipitate was dispersed in 250 ml of solution.
[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0037] The PDA-Ppy-Ti3C2T x (MXene) water-based anti-corrosion coating, adding a small amount of evenly dispersed PDA-Ppy-Ti3C2T x (MXene) composites can significantly improve the barrier capacity, mechanical properties and corrosion resistance of the coating. x The excellent water solubility of (MXene) makes the composite more evenly dispersed, avoids agglomeration, and greatly improves the barrier performance of the coating. After in-situ compounding with dopamine and pyrrole, Ti3C2T x The surface of (MXene) is covered with a dense polymer layer to avoid the x (MXene) contact with oxygen enhances the Ti3C2T x The oxidation resistance of (MXene) is enhanced. At the same time, it cooperates with the corrosion inhibition of polydopamine and the passivation of polypyrrole, thereby greatly improving the long-term corrosion resistance of the coating. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0040] The coating performance test in the embodiments of the present invention is carried out according to the following standards:
[0041] Water resistance is measured according to GB / 1733-1993;
[0042] Acid resistance is measured according to GB / T9274-1988;
[0043] Alkali resistance is measured according to GB / T9274-1988;
[0044] Salt spray resistance is measured according to GB / T1771-2007.
[0045] Example 1
[0046] 10 parts by mass of PDA-Ppy-Ti3C2T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion and stirred for 40 minutes at 500 rad / min to mix evenly. Then 1.5 parts by mass of defoamer, 0.5 parts by mass of leveling agent and 0.5 parts by mass of dispersant were added thereto and mixed evenly to obtain a PDA-Ppy- Ti3C2T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0047] Preparation of Ti3C2T x Dispersion: You can buy Ti3C2T x The mixture was mixed with water and ultrasonically treated for 2-4 h under N2 protection. The dispersion was then centrifuged at 5000 rpm for 30-60 min and the upper layer of the dispersion was collected to obtain 4 g / L Ti3C2T x Aqueous dispersion;
[0048] Ti3C2T can also be prepared by the following method x Aqueous dispersion:
[0049] (a) 3.12 g of LiF and 40.00 ml of 12 M HCl were mixed in a plastic container and stirred at 4-25° C. for 0.5-2 h to form a mixed solution;
[0050] (b) then adding 2.0 g of Ti3AlC2 powder to the mixed solution in (a) and stirring at 40-60°C for 48.0-72 h;
[0051] (c) centrifuging the mixed solution obtained in (b) at a speed of 5000-7000 rpm, collecting the bottom precipitate, transferring it into 100 ml of 2 mol / L HCl and stirring it for 120-360 min;
[0052] (d) Centrifuge the mixed solution after stirring in (c) at 5000 rpm for 5-30 min, pour out the supernatant, and redisperse the precipitate with deionized water. Repeat several times until the pH value of the dispersion is ≥5;
[0053] (e) The dispersion (d) was diluted to 4 g / L with deionized water and subjected to ultrasonic treatment for 2-4 h under N2 protection. The dispersion was then centrifuged at 5000 rpm for 30-60 min and the upper layer of the dispersion was collected to obtain Ti3C2T x Aqueous dispersion.
[0054] The above PDA-Ppy-Ti3C2T x The preparation method of (MXene) dispersion is as follows:
[0055] (1) 0.1 g of pyrrole monomer was completely dissolved in 10 ml of a mixture of water and ethanol (1:1) to obtain a polypyrrole dispersion; this dispersion was then added to 50 ml of the prepared 4 g / L Ti3C2T x For dispersion, the mixture was placed at 4 °C for 12 h;
[0056] (2) adding 10 ml of 0.1 g ferric chloride / 10 ml aqueous solution to 60 ml of the mixture after standing in step (1) to react at 4° C. for 12 h. After the reaction is completed, the suspension is centrifuged at 5000 rpm for 5 minutes, and the bottom precipitate is collected and rinsed three times with deionized water to remove unreacted pyrrole monomer;
[0057] (3) 1 g Ppy-Ti3C2T x The (MXene) precipitate was ultrasonically dispersed in 250 ml of deionized water for 30 min to obtain a 4 g / ml dispersion. Then, 0.06 g of tromethamine was dissolved in 50 ml of the dispersion, and 0.1 mol / L hydrochloric acid was gradually added to the solution until the pH reached 8.5.
[0058] (4) Add 0.1 g of dopamine hydrochloride to the 62.5 ml mixed solution after adjusting the pH value in step (3) for reaction at 4 °C for 24 h. After the reaction is completed, centrifuge the suspension at 5000 rpm for 5 minutes to collect the PDA-PANI-Ti3C2T x The precipitate was washed three times with deionized water to remove the unreacted dopamine hydrochloride. xThe MXene solid product was prepared by ultrasonic dispersion in 250 ml of deionized water for 30 min to obtain 4 mg / ml of PDA-Ppy-Ti3C2T x (MXene) dispersion.
[0059] Example 2
[0060] 20 parts by mass of PDA-Ppy-Ti3C2T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion and stirred at 500 rad / min for 40 min to mix evenly. Then 0.5 parts of defoamer, 1.5 parts of leveling agent and 0.5 parts of dispersant were added thereto and mixed evenly to obtain a PDA-Ppy-Ti3C2T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0061] The above PDA-PANI-Ti3C2T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0062] Example 3
[0063] 30 parts by mass of PDA-Ppy-Ti3C2T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion, and stirred for 40 min at 500 rad / min to mix evenly. Then, 0.5 parts by mass of defoamer, 0.5 parts by mass of leveling agent, and 1.5 parts by mass of dispersant were added thereto and mixed evenly to obtain a PDA-Ppy-Ti3C2T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0064] The above PDA-PANI-Ti3C2T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0065] Example 4
[0066] 40 parts by mass of PDA-Ppy-Ti3C2T xThe (MXene) dispersion was added to the aqueous polyurethane and stirred at 500 rad / min for 40 min to mix evenly. Then, 1.0 parts of defoamer, 0.5 parts of leveling agent, and 1.0 parts of dispersant were added thereto and mixed evenly to obtain a PDA-Ppy-Ti3C2T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0067] The above PDA-PANI-Ti3C2T x The preparation steps of the MXene composite dispersion are consistent with those in Example 1.
[0068] Example 5
[0069] 50 parts by mass of PDA-Ppy-Ti3C2T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion and stirred at 500 rad / min for 40 min to mix evenly. Then 1.5 parts by mass of defoamer, 1.5 parts by mass of leveling agent and 1.5 parts by mass of dispersant were added thereto and mixed evenly to obtain a PDA-Ppy-Ti3C2T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0070] The above PDA-PANI-Ti3C2T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0071] Comparative Example 1
[0072] 100 parts by mass of waterborne polyurethane, add 1.5 parts by mass of defoamer, 1.5 parts by mass of leveling agent, and 1.5 parts by mass of dispersant at 500 rad / min, stir for 40 minutes to mix evenly. Apply it on tinplate and glass sheet, put it in a 35℃ oven, and form a transparent paint film after the water evaporates. The formed paint film is tested after 7 days of maintenance at room temperature, and its performance is shown in Table 1.
[0073] Comparative Example 2
[0074] 20 parts by mass of MXene dispersion (4 g / L Ti3C2T xAdd 100 parts by mass of waterborne polyurethane to the aqueous solution, stir for 40 minutes at 500 rad / min. Then add 1.5 parts by mass of defoamer, 1.5 parts by mass of leveling agent, and 1.5 parts by mass of dispersant, stir for 40 minutes to mix evenly. Apply it on tinplate and glass sheet, put it in a 35℃ oven, and form a transparent paint film after the water evaporates. The formed paint film was tested after 7 days of maintenance at room temperature, and its performance is shown in Table 1.
[0075] Table 1 shows the test results of coating performance obtained in Comparative Examples 1 and 2 and Examples 1 to 5
[0076]
[0077] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A modified Ti3C2T x The water-based polyurethane anti-corrosion coating comprises water-based polyurethane, PDA-Ppy-Ti3C2T x Compounds, defoamers, leveling agents, dispersants; The PDA-Ppy-Ti3C2T x The composite dispersion is prepared by the following steps: (1) The pyrrole monomer is completely dissolved in the mixed solution to obtain a polypyrrole dispersion, which is then added to the Ti3C2T x Aqueous dispersion, and the mixture is allowed to stand; (2) adding an aqueous solution of ferric chloride to the mixture after standing in step (1) to react, and after the reaction is completed, centrifuging, collecting and washing the bottom precipitate to remove unreacted pyrrole monomer; (3) dispersing the precipitate washed in step (2) in water to obtain a dispersion, dissolving tromethamine in the dispersion, and adjusting the pH value of the mixed solution; (4) Add dopamine hydrochloride to the mixed solution after adjusting the pH value in step (3) to react. After the reaction is completed, centrifuge and collect the PDA-Ppy-Ti3C2T x The precipitate was washed to remove the unreacted dopamine hydrochloride, and finally the precipitate was dispersed in water to obtain PDA-Ppy-Ti3C2T x Composite dispersion.
2. A modified Ti3C2T-containing polymer according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized in that: It includes the following components by mass: 100 parts of waterborne polyurethane; PDA-Ppy-Ti3C2T x 10-50 parts of composite dispersion; Defoaming agent 0.1-2 parts; 0.1-2 parts of leveling agent; Dispersant 0.1 to 2 parts.
3. A modified Ti3C2T-containing polymer according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The waterborne polyurethane is selected from F0401 or F0402; The defoamer is a white mineral oil defoamer; The leveling agent is a fluorocarbon leveling agent; The dispersant is an unsaturated polycarboxylic acid polymer solution.
4. A modified Ti3C2T-containing polymer according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The waterborne polyurethane is F0401 emulsion; The leveling agent is OP-8035 / KH leveling agent; The dispersant is BYK163.
5. A modified Ti3C2T-containing polymer according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized in that: Prepared by the following steps: PDA-Ppy-Ti3C2T x The composite dispersion is added to the aqueous polyurethane emulsion and mixed evenly, and then a defoamer, a leveling agent and a dispersant are added thereto and mixed evenly to obtain a PDA-Ppy-Ti3C2T x Water-based polyurethane anti-corrosion coating.
6. A modified Ti3C2T-containing according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The mixed solution in step (1) is a mixture of water and ethanol, wherein the volume ratio of water to ethanol is 1:1; The amount ratio of the pyrrole monomer and the mixed solution in step (1) satisfies: 0.1-0.5 g of pyrrole monomer is added for every 10 ml of the mixed solution; The polypyrrole dispersion and Ti3C2T x The volume ratio of the aqueous dispersion is 1:5; The static condition described in step (1) is to place at 4-12°C for 12-48 hours; Ti3C2T described in step (1) x Dispersion refers to the Ti3C2T x Dispersed in water, and treated with ultrasound under N2 protection to obtain 2-4 g / L Ti3C2T x Aqueous dispersion.
7. A modified Ti3C2T-containing material according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The ferric chloride aqueous solution in step (2) is prepared by adding 0.1-0.5 g of ferric chloride per 10 ml of aqueous solution; the volume ratio of the ferric chloride aqueous solution to the mixture is 1:6; The reaction conditions in step (2) are 4-12° C. for 12-48 hours; The washing described in step (2) refers to washing the precipitate with water or anhydrous ethanol.
8. The modified Ti3C2T-containing polymer according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The amount of water used in step (3) is such that 250 ml of water is added for every 1 g of precipitation; The amount of tromethamine used in step (3) satisfies the requirement that 2.5-7.5 L of dispersion liquid is used for every 3-9 g of tromethamine; The pH value in step (3) is adjusted by 0.1 mol / L hydrochloric acid to a pH range of 8-9.
9. A modified Ti3C2T-containing material according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The amount of dopamine hydrochloride used in step (4) satisfies the requirement that 0.625-3.125 L of the mixed solution is used for every 1-5 g of dopamine hydrochloride.
10. The modified Ti3C2T-containing polymer according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The reaction conditions in step (4) are 4-30°C for 12-48 hours; The washing described in step (4) refers to washing the precipitate with water or anhydrous ethanol; PDA-Ppy-Ti3C2T described in step (4) x Dispersion liquid is 1gPDA-PANI-Ti3C2T x The precipitate was dispersed in 250 ml of solution.
Citation Information
Patent Citations
Preparation method of MXene-based electromagnetic shielding coating material
CN110117431A
Flexible PPy / MXene-PDA photo-thermal fabric for solar evaporator and preparation method thereof
CN113882154A